(untitled) (Applied History Journal of Merong Mahawangsa, 2025)
Kepentingan penghayatan sejarah kepada generasi muda Malaysia sering terabai dan dianggap tidak penting dalam menelusuri arus kemodenan kini. Umum tidak menyedari kepentingan penghayatan sejarah menujahkan keutuhan identiti nasional yang membawa kepada keharmonian masyarakat heterogen Malaysia. Sejarah memerlukan penghayatan yang tinggi kerana ia merupakan teras dalam memastikan semua warganegara memiliki identiti nasional yang unggul. Justeru, makalah ini akan membincangkan mengenai trend di peringkat global mengenai penyelidikan sejarah dan identiti nasional, seterusnya perkaitan antara sejarah dan identiti nasional serta kepentingannya kepada generasi muda. Pengumpulan data adalah secara analisis bibliometrik dari pangkalan data Scopus yang melibatkan 67 artikel jurnal berbahasa Inggeris dari penerbitan 5 tahun terkini (2019-2024). Dapatan membincangkan trend penerbitan mengikut tahun, negara dan tema/kata kunci serta membincangkan perkaitan antara sejarah dan identiti nasional serta kepentingannya kepada generasi muda. Implikasinya, penyelidikan berkaitan sejarah dan identiti nasional dalam kalangan generasi muda perlu diperluaskan memandangkan generasi ini adalah pemangkin kepada kemajuan negara melalui identiti negara merdeka. ABSTRACT The importance of historical appreciation among the younger generation in Malaysia is often overlooked and deemed insignificant in navigating the currents of modernity. People does not realise the importance of historical appreciation in strengthening national identity, which lead to fostering harmony within Malaysia’s heterogeneous society. History is not merely as enhancing knowledge and understanding; rather, a profound appreciation of the nation’s history serves as a cornerstone in ensuring that all citizens embody a strong sense of national identity. Therefore, this paper will discuss global trends in historical research and national identity, as well as the relationship between history and national identity and its relevance to the younger generation. Data collection was conducted through bibliometric analysis using the Scopus database, analysing 67 English-language journal articles published over the past five years (2019–2024). The findings explore publication trends by year, country, and theme/keywords, while also emphasizing the connection between history and national identity and its significance for the younger generation. Implication, research on history and national identity among the younger generation needs to be intensified, as this generation plays a pivotal role in driving the nation’s progress and embodying the identity of an independent country.